Pharyngeal carriage of Neisseria meningitidis in 2—19-year-old individuals in Uganda - Cauganta, Dominique A.; Foggd, Carole; Bajunirwe, Francis; Piola, Patrice; Twesigye, Rogers; Mutebi, Fred; Frøholma, L. Oddvar; Rosenqvist, Einar; Batwala, Vincent; Aaberge, Ingeborg S.; Rottingen, John-Arne; Guerin, Philippe J. (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2006)
In southern Uganda, only sporadic cases of serogroup A meningococcal disease have been reported since 2000. As part of an immunogenicity study of the tetravalent meningococcal polysaccharide vaccine, nasopharyngeal swab samples were collected twice, 4 weeks apart, from 2—19-year-old healthy individuals in Mbarara, Uganda. Only 15 (2.0%) of the 750 individuals carried meningococci asymptomatically. Most of the strains were non-serogroupable and none were serogroup A. However, two individuals carried a serogroup W135 strain, sequence type (ST)-11, similar to the clone that was responsible for the epidemic in Burkina Faso in 2002. Our study further demonstrates the geographical spread of serogroup W135 ST-11 strain and thus the potential epidemic risk.
Keywords: Neisseria meningitidis; Meningococcal carriage; Serogroup W135; Uganda